Estimation of life expectancy and the expected years of life lost among heroin users in the era of opioid substitution treatment (OST) in Taiwan. (1st August 2015) - Chang, Kun-Chia; Lu, Tsung-Hsueh; Lee, Kuan-Ying; Hwang, Jing-Shiang; Cheng, Ching-Ming; Wang, Jung-Der
Highlights: We estimate life expectancy (LE) and expected years of life lost (EYLL) of heroin users stratified by opioid substitution treatment (OST) for comparison. We apply a novel semi-parametric method for extrapolation of the survival curves with an assumption of constant excess hazard. OST saves 7.8 EYLL more than non-OST after accounting for lead time bias. Effective suicide prevention programs could enhance its life-saving effect. The findings would be useful in future cost–utility analysis of addiction treatment. Abstract: Background: Opioid substitution treatment (OST) has been implemented in Taiwan since 2006. We estimated the life expectancy (LE) and expected years of life lost (EYLL) in a cohort of heroin users stratified by OST for comparison. Methods: A total of 1283 heroin users recruited from 2006 to 2008 were linked to the National Mortality Registry until the end of 2011. Among them, 983 received OST, while 300 did not. Kaplan–Meier estimation for survival was performed, and it was extrapolated to 50 years to obtain the LE using a semi-parametric method. We further estimated the EYLL for both cohorts by subtracting their life expectancies from the age- and sex-matched referents of the general population. Cause-specific standardized mortality ratios (SMRs) were calculated and compared with the national cohort to validate the representativeness of this sample. Results: After extrapolation to 50 years of survival, the estimated average LE and EYLL were 27.4 and 10.6 for OST subjects, respectively, while those of the non-OST were 20.2 and 18.4 years. The all-cause mortality rates (per 1000 person-years) in the observational period for the OST and non-OST group were 15.5 and 23.9, respectively, representing a 7.5- and 10.2-fold SMR compared to the general population, indicating a high representativeness for our sample. But SMR of suicide mortality elevated 16.2 and 3.1 folds in OST and non-OST group, respectively. Conclusions: OST saves 7.8 EYLL more than non-OST after accounting for lead time bias. Effective suicide prevention programs could enhance its life-saving effect, especially among those co-morbid with depressive disorders.